Positron Emission Tomographic Imaging of the Cannabinoid Type 1 Receptor System with [C]OMAR ([C]JHU75528): Improvements in Image Quantification Using Wild-Type and Knockout Mice - Raúl Herance; Santiago Rojas; Sergio Abad; Xavier Jiménez; Juan Domingo Gispert; Olga Millán; Elena Martín-García; Aurelijus Burokas; Miquel Àngel Serra; Rafael Maldonado; Deborah Pareto (Molecular Imaging)
In this study, we assessed the feasibility of using positron emission tomography (PET) and the tracer [ 11 C]OMAR ([ 11 C]JHU75528), an analogue of rimonabant, to study the brain cannabinoid type 1 (CB1) receptor system. Wild-type (WT) andCB1 knockout (KO) animals were imaged at baseline and after pretreatment with blocking doses of rimonabant. Brain uptake in WT animals was higher (50%) than in KO animals in baseline conditions. After pretreatment with rimonabant, WT uptake lowered to the level of KO animals. The results of this study support the feasibility of using PET with the radiotracer [ 11 C]JHU75528 to image the brain CB1 receptor system in mice. In addition, this methodology can be used to assess the effect of new drugs in preclinical studies using genetically manipulated animals.